Fisica em Quadrinhos: material de apoio ao professor utilizando Histórias em Quadrinhos no ensino - Alvares, Valéria (2019)
Students generally do not feel very close to physics and consider it beyond their realities and capabilities. Physics teachers can use various teaching techniques to try desmistifying this and presenting scientific knowledge in a more palatable and accessible way to students. In a world with so much technology from scientific studies that is increasingly embedded in everyday life, it is helpful to learn the principles of physics involved in these subjects and make them natural. The product described here is simple to use and could be used for engaging students in the subjects covered, as well as promoting peer interaction, which can be very helpful in teaching. Comic books can be a didactic tool, providing interesting learning resources according to Vygotsky's theories, the theorist chosen to guide the theme in question. The application of the product can be done in all grades of elementary school, from the early years to the end. We describe a teaching process that values the development of higher mental processes using thought language or written thought, materialized in comics that express internalized concepts or signs. Peer interaction is valued during the creative process, which can enhance the social aspects of those involved and promote scientific teaching using popular tools that bring ordinary people closer together.